MONITORING PENGGUNAAN AMOKSISILIN, AMPISILIN DAN KLORAMFENIKOL PADA KUCING DI RUMAH SAKIT HEWAN-FAKULTAS KEDOKTERAN HEWANUNIVERSITAS GADJAH MADA TAHUN 2005-2007 - Yanuartono . (Jurnal Sain Veteriner, 2008)
The use amoxicillin, ampicillin and chloramphenicol for cats in animal hospital, Faculty of Veterinary Medicine,Gadjah Mada University, was studied during 2005 - 2007. The use of amoxcicillin in cats was formed to be8,06%,11,78%, and 18,97% in 2005, 2006, and 2007, respectively. The values for amoxcicillin were 30,99%,24,95%, and 12,37%, while for chloramphenicol were 3,92%, 4,59%, and 8,86%. Data showed that the use ofamoxicillin and chloramphenicol were increased, however, the use of ampicillin was decreased year by year.The result of study showed that use of antibiotic in animal hospital, Faculty of Veterinary Medicine, GadjahMada University did not very very much. Besides amoxicillin, ampicillin and chloramphenicol, oxytetracyclin,enrotloxacin and cyprotloxacin were used in small percentage.Key words: amoxicillin, ampicillin, chloramphenicol, cats